1970
DOI: 10.31055/1851.2372.v49.n4.9884
|View full text |Cite
|
Sign up to set email alerts
|

Análisis fitolíticos de las principales especies de palmeras (Arecaceae) presentes en regiones subtropicales de América del Sur

Abstract: El continente sudamericano aparece como uno de los mayores centros de riqueza ydiversidad de la familia Arecaceae. Las palmeras se caracterizan por la presencia de fitolitos denaturaleza silícea denominados stegmatas, los mismos presentan características particulares quepermiten identificar a gran parte de los miembros de esta familia. El objetivo del presente trabajo es,describir las asociaciones fitolíticas de especies de palmeras y buscar el valor diagnóstico de las mismasa través de un análisis biométrico,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…Benvenuto et al . () used a combination of quantitative and qualitative variables to describe globular echinate phytoliths in ten mostly subtropical South American palm species, focusing on length and density of the ‘spines’ (for which there is, as yet, no standardized terminology) and Patterer () performed multivariate analysis on an almost identical taxonomic sample and demonstrated that phytolith diameter was especially useful for grouping related species and genera. Bowdery () also tried to differentiate globular echinate phytoliths and, using a reference collection of 29 palm species of pan‐Pacific distribution, she was able to identify six species from phytoliths recovered from sediment samples.…”
Section: Introductionmentioning
confidence: 99%
“…Benvenuto et al . () used a combination of quantitative and qualitative variables to describe globular echinate phytoliths in ten mostly subtropical South American palm species, focusing on length and density of the ‘spines’ (for which there is, as yet, no standardized terminology) and Patterer () performed multivariate analysis on an almost identical taxonomic sample and demonstrated that phytolith diameter was especially useful for grouping related species and genera. Bowdery () also tried to differentiate globular echinate phytoliths and, using a reference collection of 29 palm species of pan‐Pacific distribution, she was able to identify six species from phytoliths recovered from sediment samples.…”
Section: Introductionmentioning
confidence: 99%
“…starch grains ( algarrobo ; Giovannetti et al 2008) in five sites (Maitencillo-7, VEE, Pintados de Quiles, Talhuenal de Quiles, and Roca de Quiles), which were also found in residues adhering to a polished stone from the Tamaya-1 site. A globular echinate morphotype, found in leaves of the Chilean palm ( Jubaea chilensis ; Patterer 2014), was identified at two sites (VEE and Don Wilson); phytoliths from Cyperaceae were also found at two sites (Don Wilson and Cutana). Isolated microfossils of Amaranthaceae-Chenopodiaceae and Tropeolaceae (VEE), Festucoideae (Rocas de Quiles), and a starch grain from an undetermined tuber (Talhuenal de Quiles) were also found.…”
Section: Resultsmentioning
confidence: 99%
“…To describe the morphology and attributes of the microfossils, we used the International Code for Phytolith Nomenclature 1.0 (Madella et al 2005), International Code for Starch Nomenclature ([ICSN] 2011), and Franceschi and Horner's (1980) description of crystals. We consulted some reference collections (Albornoz 2015; Gili et al 2016; Giovannetti et al 2008; Korstanje and Babot 2007; Patterer 2014). All microfossils were measured and recorded photographically.…”
Section: Methodsmentioning
confidence: 99%
“…The use of fine details as overall geometry, detailed surface ornamentation, including the density and morphology of the dents and peaks on the phytolith surface, has proven useful in the identification of six palm species from sediment samples of pan-Pacific distribution [218]. The application of multivariate analysis on phytolith diameter in identical taxonomic samples of main palm species from subtropical regions of South America proved useful for taxonomic distinction [220]. A study from the Indian subcontinent on Chloridoideae grasses revealed that saddle shaped phytoliths are characteristic of this subfamily [221].…”
Section: Functions Of Phytolithsmentioning
confidence: 99%